ACTIVE MODERN NEOLOGISMS IN OUR SPEECH APPLICATION - Nilufar, Urazimbetova (Journal of Higher Education and Academic Advancement, 2024)
This article describes the classification of neologisms that have recently entered our language and their activity in speech. Neologisms in the article are mainly borrowed from Russian and EnglishAdd Contributor